Gravity-driven microfiltration pretreatment for reverse osmosis (RO) seawater desalination: Microbial community characterization and RO performance - Wu, Bing (2017)
A pilot gravity-driven microfiltration (GDM) reactor was operated on-site for over 250 days to pretreat seawater for reverse osmosis (RO) desalination. The microbial community analysis indicated that the dominant species in the pilot GDM system (~ 18.6 L/m2 h) were completely different from those in the other tested GDM systems (~ 2.7–17.2 L/m2 h), operating on the same feed. This was possibly due to the differences in available space for eukaryotic movement, hydraulic retention time (i.e., different organic loadings) or operation time (250 days vs. 25–45 days). Stichotrichia, Copepoda, and Pterygota were predominant eukaryotes at genus level in the pilot GDM. Furthermore, the GDM pretreatment led to a significantly lower RO fouling potential in comparison to the ultrafiltration (UF) system. This was attributed to the fact that GDM filtration produced a permeate with less amount of assimilable organic carbon (AOC) and biopolymers. Accordingly, lower amount of organic foulants (biopolymers and low molecular weight neutrals) and less biofilm formation on the GDM-RO membrane were observed. Although α-proteobacteria were dominant in both RO fouling layers, their bacterial community compositions at genus level were significantly different. Thalassobius had higher abundance in the GDM-RO fouling layers, while Erythrobacter and Hyphomonas were more predominant in the UF-RO fouling layers.